ANALISIS LAJU PERTUMBUHAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA BALIKPAPAN - Astuti, Wigi; Yudea, Yudea (FORUM EKONOMI, 2016)
This study aims to determine the rate of growth of land and building tax Rural and Urban (PBB-P2) from 2012 to 2014 and also aims to determine the contribution of the UN-P2 against revenue (PAD) Balikpapan. The analytical method used is descriptive quantitative research. Research is known that the rate of growth and the contribution of the UN-P2 fluctuated against the PAD during the years 2012-2014. It is recommended that Local Government City of Balikpapan provide counseling on a regular basis to the public, improve service performance and the need to apply sanctions for violators of tax laws so that people are aware and termovitasi to pay taxes.Keyword: Land and Building Tax Rural and Urban (PBB-P2), Growth, Contributions and revenue (PAD)